2009
DOI: 10.1007/s11224-009-9502-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and spectra studies on Zn(II) and Cu(II) complexes with thiocarbamide ligand containing Schiff base group

Abstract: The ligand of 4-phenyl-1-(1-phenylethylidene) thiosemicarbazide (HL) and its metal complexes of ZnL 2 (1) and CuL 2 (2) have been synthesized. Elemental analysis, IR and X-ray single crystal diffraction characterizations for 1 and 2 have been carried out. In the complexes 1 and 2, the central metallic ions Zn 2? and Cu 2? , coordinate with two deprotonated ligands, L -, respectively and adopt distorted tetrahedral geometries. The thermal analyses result shows that the two complexes undergo two similar decompos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…The chelate/chelate angles in the literature structures vary from 60.10(5) to 89.65(5)°. Interestingly, these angles are calculated for the two independent molecules in the asymmetric unit of the complex with R 1 = R 4 = Ph and R 2 = Me [13], suggesting an influence of molecular packing effects on the adopted conformation.…”
Section: Commentmentioning
confidence: 95%
“…The chelate/chelate angles in the literature structures vary from 60.10(5) to 89.65(5)°. Interestingly, these angles are calculated for the two independent molecules in the asymmetric unit of the complex with R 1 = R 4 = Ph and R 2 = Me [13], suggesting an influence of molecular packing effects on the adopted conformation.…”
Section: Commentmentioning
confidence: 95%
“…R 0 = R 00 = Ph for the R = 3-FPh compound (Ferraz et al, 2012) or mixed alkyl/aryl, i.e. R 0 = Me and R 00 = Ph for the R = Ph compound (Wang et al, 2009); the latter structure has two molecules in the asymmetric unit. The R 0 and R 00 groups can be part of a ring, e.g.…”
Section: Database Surveymentioning
confidence: 99%
“…All of these synthesized chelate ligands possess two potential coordinating sites, respectively, each of which can bite with a metallic ion to construct a metal complex having five-membered rigid chelate ring. The experimental results show that some so-synthesized ligands and their metal complex can emit green and blue fluorescence [16], which provide a facile method to obtain the blue-emitting complexes. Herein, we wish to report another Schiff base ligand of 4-phenyl-1-(4-methoxyl-1-phenylethylidene)thiosemicarbazide (HL) and its chelate complexes of ZnL 2 (1), NiL 2 (2), and CuL 2 (3), including their crystal structures, UV-Vis spectra, fluorescence spectra, thermal stabilities, and electrochemical behaviors.…”
Section: Introductionmentioning
confidence: 97%
“…Especially, Schiff base metal-chelate complexes have been found to exhibit good luminescent properties [11][12][13][14][15][16]. For example, in 2001, Liu group reported that N,N 0 -disalicylidene-triethylenetetramine zinc(II) complex showed bright blue photoluminescence [13].…”
Section: Introductionmentioning
confidence: 99%